Water resource management in rural areas: A case study in Kuching District, Sarawak, Malaysia - Juki, anak Endok. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Water covers more than 75 percent of the earth surface. About 94 percents of water is found in ocean as salt water while the rest of the water is found on the continents as fresh water. However, out of the available fresh water on the continent, 95 percent is stored as ground water or in glaciers and inland ice. Only a small fraction of the total freshwater on earth water can be used by human. Besides being the basic element to sustain lives, it is also necessary to support the other living organism. water cannot be created nor destroyed. The quantity remians the same within the hydrological cycles overs billions of years. with increasing populations, the demand for water also increases.